2017
DOI: 10.1038/bjc.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of R-spondins in triple-negative and metaplastic breast cancers

Abstract: Background:RSPO ligands, activators of the Wnt/β-catenin pathway, are overexpressed in different cancers. The objective of this study was to investigate the role of RSPOs in breast cancer (BC).Methods:Expression of RSPO and markers of various cancer pathways were measured in breast tumours and cell lines by qRT–PCR. The effect of RSPO on the Wnt/β-catenin pathway activity was determined by luciferase assay, western blotting, and qRT–PCR. The effect of RSPO2 inhibition on proliferation was determined by using R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…In mice mammary gland, Lgr5 + cells are chiefly within the Lin − CD24 + CD49f high subpopulation; they can differentiate into both basal and luminal mammary epithelial cells, and regenerate functional mammary glands . In human breast cancers, both Lgr5 and Rspo are overexpressed with activation of the Wnt/β‐catenin pathway, which contributes to increased tumor growth, metastasis and stemness . Tenascin C (TNC) is an extracellular matrix protein abundantly expressed by mammary stem cells .…”
Section: Wnt Signaling Enriches Progenitor Cells/cancer Stem Cells Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice mammary gland, Lgr5 + cells are chiefly within the Lin − CD24 + CD49f high subpopulation; they can differentiate into both basal and luminal mammary epithelial cells, and regenerate functional mammary glands . In human breast cancers, both Lgr5 and Rspo are overexpressed with activation of the Wnt/β‐catenin pathway, which contributes to increased tumor growth, metastasis and stemness . Tenascin C (TNC) is an extracellular matrix protein abundantly expressed by mammary stem cells .…”
Section: Wnt Signaling Enriches Progenitor Cells/cancer Stem Cells Inmentioning
confidence: 99%
“…37,38 In human breast cancers, both Lgr5 and Rspo are overexpressed with activation of the Wnt/β-catenin pathway, which contributes to increased tumor growth, metastasis and stemness. 39,40 Tenascin C (TNC) is an extracellular matrix protein abundantly expressed by mammary stem cells. 41 Produced by breast cancer cells in which~90% is CD44 + CD24 − , TNC maintains the expression of Lgr5 and the response of Lgr5 to Wnt ligands, and is associated with aggressive lung metastasis.…”
Section: Wnt Signaling E Nriche S Progenitor Cells/ Cancer Stem Celmentioning
confidence: 99%
“…Previous studies have revealed that Lgr6 activates multiple signaling pathways, including the Wnt/β-catenin pathway (34,37); however, no studies have focused on its role in activating the PI3K/AKT pathway in cRc. In the present study, AKT/PI3K was inactivated when Lgr6 was inhibited by siRNA, indicating that the role of Lgr6 in cRc may partly depend on the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Note that all of these components function at the level of ligand and receptor binding. The top two hits, RSPO2 and FZD6, have both been linked to reduced metastasis free survival, but likely operate via different WNT signaling mechanisms (Corda et al, 2017;Coussy et al, 2017). It should be stressed that in this respect, breast cancer is not unique.…”
Section: Is Wnt Signaling Deregulated In Human Breast Cancers?mentioning
confidence: 99%
“…In contrast, copy number gain of the FZD6 gene, which can be readily detected in human breast cancer cohorts ( Figure 1B) and most predominantly in TNBC, most likely exerts its effects on cell motility and invasion via alternative, non-canonical WNT signaling mechanisms (Corda et al, 2017). For other components, such as RSPO2, RSPO4 and to a lesser extent LGR5 and LGR6, the overexpression of which is enriched in TNBC, the mechanism is more likely to involve amplification of the WNT/CTNNB1 signaling response (Coussy et al, 2017). Importantly, the separation between canonical and non-canonical WNT signaling is not black and white.…”
Section: Genementioning
confidence: 99%